Thermal analysis of laser irradiation-gold nanorod combinations at 808 nm, 940 nm, 975 nm and 1064 nm wavelengths in breast cancer model. (1st January 2021) - Bianchi, Leonardo; Mooney, Rachael; Cornejo, Yvonne R.; Schena, Emiliano; Berlin, Jacob M.; Aboody, Karen S.; Saccomandi, Paola
Abstract: Background: Photothermal therapy is currently under the spotlight to improve the efficacy of minimally invasive thermal treatment of solid tumors. The interplay of several factors including the radiation wavelengths and the nanoparticle characteristics underlie the thermal outcome. However, a quantitative thermal analysis in in vivo models embedding nanoparticles and under different near-infrared (NIR) wavelengths is missing. Purpose: We evaluate the thermal effects induced by different combinations of NIR laser wavelengths and gold nanorods (GNRs) in breast cancer tumor models in mice. Materials and methods: Four laser wavelengths within the therapeutic window, i.e., 808, 940, 975, and 1064 nm were employed, and corresponding GNRs were intratumorally injected. The tissue thermal response was evaluated in terms of temperature profile and time constants, considering the step response of a first-order system as a model. Results: The 808 nm and 1064 nm lasers experienced the highest temperature enhancements (>24%) in presence of GNRs compared to controls; conversely, 975 nm and 940 nm lasers showed high temperatures in controls due to significant tissue absorption and the lowest temperature difference with and without GNRs (temperature enhancement <10%). The presence of GNRs resulted in small time constants, thus quicker laser-induced thermal response (from 67 s to 33 s at 808 nm). Conclusions: The thermal responses of different GNR-laser wavelength combinations quantitatively validate the widespread usage of 808 nm laser for nanoparticle-assisted photothermal procedures. Moreover, our results provide insights on other usable wavelengths, toward the identification of an effective photothermal treatment strategy for the removal of focal malignancies.